1981
DOI: 10.4153/cjm-1981-080-0
|View full text |Cite
|
Sign up to set email alerts
|

On an Irreducibility Theorem of A. Cohn

Abstract: In [1, b.2, VIII, 128] Pólya and Szegö give the following interesting result of A. Cohn:THEOREM 1. If a prime p is expressed in the decimal system asthen the polynomial irreducible inZ[x].The proof of this result rests on the following theorem of Pólya and Szegö [1, b.2, VIII, 127] which essentially states that a polynomial f(x) is irreducible if it takes on a prime value at an integer which is sufficiently far from the zeros of f(x).THEOREM 2. Let f(x) ∊ Z[x] be a polynomial with the zeros α1, α2, …, αn. If … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 2 publications
0
31
0
Order By: Relevance
“…Indeed, if / = gh is a non-trivial factorization of / in Z[X] then g(rn)h(rri) = f(m) = n is a non-trivial Splitting of n in Z. This result follows from the proofs in [4], where we need only the easier case m > 3. We note that / can be factored in time (logn)O(1\ by means of the algorithm of [21].…”
Section: Finding a Polynomialmentioning
confidence: 50%
“…Indeed, if / = gh is a non-trivial factorization of / in Z[X] then g(rn)h(rri) = f(m) = n is a non-trivial Splitting of n in Z. This result follows from the proofs in [4], where we need only the easier case m > 3. We note that / can be factored in time (logn)O(1\ by means of the algorithm of [21].…”
Section: Finding a Polynomialmentioning
confidence: 50%
“…There are several results in the literature (see [7], [8], [9], and the references in those papers) which say that under appropriate conditions, if f(k) is prime, then/(x) is irreducible. (In [9], f(k) has to be prime for several values of k, actually.)…”
mentioning
confidence: 99%
“…Indeed, the derivative of this function is 3x 2 − 2x = x(3x − 2), revealing that The foregoing proof of Theorem 2 is really a motivated account of the proof in [1], where the authors adapted the method indicated in [5, p. 133] to deal with the general base. Our approach has been more naive and slightly different.…”
Section: Lemma 3 Suppose That α Is a Complex Root Of A Polynomialmentioning
confidence: 99%
“…This problem was subsequently generalized to any base b by Brillhart, Filaseta, and Odlyzko [1]. We will give a proof of this fact that is conceptually simpler than the one in [1], as well as study the analogue of this question for function fields over finite fields. More precisely, let F q denote the finite field of q elements, where q is a prime power.…”
mentioning
confidence: 99%